Management of Macular Hemorrhage (Springer International Publishing, 2018)
Sub- or preretinal hemorrhage involving the macula is a typical complication in a variety of ocular diseases, including age-related macular degeneration, arterial macroaneurysm, Valsalva retinopathy, and trauma. However, there is currently no consensus regarding the ideal treatment for macular hemorrhage. The purpose of this book on macular hemorrhage is twofold: it aims both to impart valuable information on pathophysiology, risk factors, diagnostic aspects, and prognostic criteria under different conditions and to provide a systematic overview of therapeutic approaches that cover the most important situations a vitreoretinal surgeon might encounter when treating patients with this disorder. Case presentations, clinical photographs, and an extensive review of the literature supplement the important information on clinical decision making, surgical techniques, and typical pitfalls and invite the reader to explore the advantages and disadvantages of various approaches to the management of macular hemorrhage.